Clinical analysis of pregnancy complicated with miliary tuberculosis - Kaige Wang; Donghua Ren; Zhixin Qiu; Weimin Li (Annals of Medicine, 2022)
Background Pregnancy complicated with tuberculosis is increasingly common. The clinical characteristics of pregnancy complicated with miliary tuberculosis are summarized in this study. Methods A retrospective analysis of pregnant patients with miliary tuberculosis was performed in terms of epidemiology, demography, clinical characteristics, laboratory tests, treatment, and prognosis. Results Of the 23 patients that were included, 12 became pregnant after in vitro fertilization combined with embryo transfer (IVF-ET). The average gestational age at symptom onset was 13.96 weeks, and the average time from symptom onset to diagnosis was 33 days. Clinical symptoms included fever, dyspnoea, cough, headache, abdominal pain, and chest pain. Extrapulmonary tuberculosis occurred in 10 patients, respiratory failure in 11 patients, and ARDS in 9 patients. Chest HRCT showed diffusely distributed miliary nodules in all patients. Six patients were on mechanical ventilation, two underwent ECMO, and one died. Symptoms appeared in the first trimester of nine pregnancies after IVF-ET and in the second trimester of seven natural pregnancies. Conclusions Miliary tuberculosis can occur in pregnant patients, especially in patients after IVF-ET. Symptoms often appear in the first trimester of pregnancy after IVF-ET and in the second trimester of natural pregnancy. Lacking specificity, the common clinical characteristics include elevated inflammation markers, anaemia, low lymphocyte count, and multiple miliary nodules shown on a chest HRCT scan. Half of patients with miliary tuberculosis may develop respiratory failure, and some may progress to ARDS. Therefore, infertile patients should be required to undergo TB screening before undergoing IVF-ET, and preventive anti-TB treatment should be given to patients with latent TB infections or untreated TB disease.Key Message Miliary tuberculosis can occur in pregnant patients, especially in pregnant patients after IVF-ET. Symptoms often appear in the first trimester of pregnancy after IVF-ET and in the second trimester of natural pregnancy. Many patients develop respiratory failure or ARDS.